Orthognathic surgery case overview in patients with class III dentoskeletal Angle classification - Hutomo, Dimas Ilham; Astuti, Ida Ayu; Sumaji, Borman (Universitas Padjadjaran, 2013)
Introduction: Angle classification is a classification commonly used for malocclusion in the field of orthodontics. Mandibular prognation is one of the skeletal features of Class III dentoskeletal classification or defined as mesiocclusion. The prevalence of class III dentoskeletal occurrence in Asian populations is much higher than Caucasian racial populations. Aim of research is to obtain data of Orthognathic surgery case overview in patients with class III dentoskeletal angle classification Methods: Type of research is using a retrospective descriptive method by taking secondary data from medical record cards of orthognathic surgery cases. The population in this study were all medical record data of patients undergoing orthognathic surgical treatment in the Oral and Maxillofacial Surgery Department of RSUP Dr. Hasan Sadikin 2006-2011 period. The sample in this study is medical record data of patients with Class III dentoskeletal classification performed orthognathic surgery in the period 2006-2011. then classified by year of surgery, sex, age, Angle classification, state of anterior open bite, location of surgery, and technique used in surgery. Result: 2% of orthognathic surgical patients have a Class III Angle relationship and only 8% of orthognathic surgical patients have a Class II Angle relation. Based on the anterior tooth overbite relation in patients with an Angle class III relationship, there are 16 patients who have an open bite relation on the anterior teeth. Only 8 patients from Angle III class relationships were treated with orthognathy without an anterior open bite relation.Conclusion: In the period 2006-2011, the Department of Oral and Maxillofacial Surgery Dr. Hasan Sadikin handled 26 orthognathic surgical patients, The most orthognathic surgical patients were in the age group of 21-25 years and the difference in the number of male and female patients was only small, Cases of orthognathic surgery in patients with class dentoskeletal Angle classification III is the most handled case by the Department of Oral and Maxillofacial Surgery Dr. Hasan Sadikin Bandung in the period 2006-2011 reached 92.31% of all orthognathic surgery cases or 24 cases. (4) Most orthognathic surgical patients with Class III dentoskeletal classification have an anterior open bite relation. The most commonly performed surgical techniques for patients with Class III dentoskeletal classification are bimaxillary surgical techniques with a combination of Le Fort 1 osteotomy techniques on the maxilla and sagittal split osteotomy and genioplasty of the mandible.